KEAP1 mutations activate the NRF2 pathway to drive cell growth and migration, and attenuate drug response in thyroid cancer - Bambach, Nicholas E.; Ricarte-Filho, Julio C.; Reichenberger, Erin R.; Hernandez-Padilla, Christian; Hinkle, Kyle; Isaza, Amber; Bauer, Andrew J.; Franco, Aime T. (Frontiers in Oncology, 2026)
The KEAP1/NRF2 pathway, a major regulator of the cellular oxidative stress response, is frequently activated in human cancers. Often mediated by loss-of-function mutations in KEAP1, this activation causes increased NRF2 transcriptional activity and constitutive activation of the antioxidant response. While KEAP1 mutations have been well documented in various cancers, their presence and role in thyroid carcinoma have remained largely unexplored. In this study, we sequenced pediatric thyroid tumors and analyzed publicly available datasets, identifying 81 KEAP1 mutations in tumors across a range of histologies. In these tumors, we further identified frequent biallelic loss of KEAP1 via 19p13.2 loss of heterozygosity (LOH). MAPK-activating alterations were found in a subset of KEAP1-mutant cases, but they were mutually exclusive with 19p13.2 LOH. Transcriptome analysis also revealed significant activation of the NRF2 pathway in KEAP1-mutant tumors. Four additional cases with similar transcriptional profiles but lacking mutational data were identified, likely representing putative KEAP1 mutants. Using in vitro cell line models, we then profiled the functional consequences of KEAP1 knockout in cells with and without known driver alterations. In these models, we show that KEAP1 loss leads to an NRF2-dependent upregulation of AKR1C3, GCLC, NQO1, and TXNRD1, along with increased proliferation and migration irrespective of MAPK mutational status. We also demonstrate that loss of KEAP1 reduces sensitivity of RET fusion-positive cells to selpercatinib, consistent with previous reports that these alterations promote drug resistance in other malignancies. In this study, we comprehensively profile KEAP1 mutations in thyroid tumors, showing that they are more prevalent and functionally significant than previously recognized. These findings position KEAP1 mutations as novel oncogenic variants in thyroid cancer and support the integration of KEAP1/NRF2 pathway profiling into future studies and clinical frameworks.